Ethics for accountants and auditors - Rossouw, Deon; Kretzschmar, Louise; Sander, Korien; Siebrits,Jacques; Voster,Paul (Oxford University Press Southern Africa (Pty) Ltd., 2019)
"Ethics for Accountants and Auditors offers an introduction to ethical value systems and ethical theories that are relevant to the accounting and auditing profession. The text combines theory and practical application to equip students and practitioners with the tools to deal with various ethical dilemmas. The book is suited for graduate and postgraduate teaching, managerial training and the ethical orientation of members of accounting and auditing professional associations."--Publisher's description.